Apakah Modal Sosial Berpengaruh Terhadap Kinerja Usaha Kecil Menengah - Wijaya, Reni; Waty, Henny (Pustaka Galeri Mandiri, 2024)
This research aims to determine the influence of social capital on the performance of MSMEs in Pariaman City. This research uses descriptive quantitative analysis methods and probability sampling methods with simple random sampling techniques on 95 respondents who are MSMEs in Pariaman City. Data were collected through questionnaires and processed using SPSS 25 with instrument tests (validity test and reliability test, and multiple linear regression test. The test results in this research have no significant effect on the performance of MSMEs in Pariaman City with a sig. value of 0.085 > 0.05 This shows that the social relationships that exist in the entrepreneurial environment of MSMEs in Pariaman City are not strong enough so that they cannot be used as social capital that can support them. improving the business performance of MSMEs in Pariaman City.